A Long-tailed Tit Aegithalos caudatus nest constructed from plastic fibres supports the theory of concealment by light reflectance. Issue 2 (3rd July 2019) - Broughton, Richard K.; Parry, Wayne
ABSTRACT: We document a highly unusual Long-tailed Tit nest in northwest England that is largely constructed from plastic debris, namely synthetic fibres, apparently from a nearby discarded cushion. We describe the nest location, its construction and its dimensions. The unusual nest material is discussed in relation to the potential insulation properties, and especially its camouflage according to the hypothesis of concealment by light reflection.